The Influence of Horizontal Communication, Upward Communication, and Downward Communication on Generation Z Employee Performance at PT Bank Mandiri Tegal Area - Fahmi Yulian Idris (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to analyze the effect of three forms of organizational communication—horizontal communication, upward communication, and downward communication—on employee performance at PT Bank Mandiri Area Tegal. This research stems from the importance of communication effectiveness in banking organizations that are hierarchical and complex, where internal communication barriers often negatively impact employee performance. The novelty of this research lies in its approach, which simultaneously examines the three directions of communication within one integrative model—a perspective that has not been comprehensively studied in the Indonesian banking sector. The method used is a quantitative approach with an explanatory research type and census technique, sampling the entire employee population of 30 people. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that the three independent variables had a positive and significant influence on employee performance. Horizontal communication contributed 27.6%, upward communication 27.9%, and downward communication 27.3% to performance improvement. This finding confirms that effective two-way and lateral communication is essential to driving productivity, engagement, and collaboration in the work environment.